IoT-based Plant Watering System - Mohd Najid @ Zakaria, Nurul Irfah; Rosli Omar (Evolution in Electrical and Electronic Engineering, 2024)
This work presents an IoT-based plant watering system using the Internet of Things (IoT) via the Nodemcu ESP32. The objectives are to design an automatic plant watering system with an ESP32 microcontroller and appropriate sensors, such as a soil moisture sensor and a humidity sensor, and integrate the Internet of Things (IoT) into the plant watering system so that the plant can grow optimally. Also, to evaluate the proposed system’s effectiveness based on the plant’s conditions on the eggplant. The scope of the study is focused on developing a prototype of an IoT-based intelligent plant watering system that detects the soil moisture level of plants on a small scale to automate the water supply and automatic liquid fertilizer. In this work, it requires Blynk application software on the smartphone and hardware implementation that can detect the condition of the plant by using the dht-11 sensor, pH sensor, and moisture level sensor. The findings of this paper are based on the experiments that were done, which show optimal conditions for plants. The Internet of Things (IoT)-based watering system continuously analyzes and reacts to a range of environmental aspects. At various times, the actions of the system are displayed. The second two experiments were between smart irrigation and normal irrigation. After 5 weeks, the results showed that smart irrigation surpassed normal irrigation. The conclusion of this paper is based on the objectives that all three objectives have already achieved.